PENERAPAN METODE BERMAIN PERAN (ROLE PLAYING) UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD ISTIANAH TERPADU KOTA SORONG - HERSEGOVINA HERSEGOVINA; AGUS YUDIAWAN; ALIF HASANAH (CV. ADIBA AISHA AMIRA, 2026)
The purpose of this study is to assess the impact of applying the Role Playing method on enhancing students' interest in learning the Indonesian Language subject for fourth-grade students at SD Istianah Terpadu, Sorong City. The role playing method, which involves students acting out various roles, can create a more engaging and meaningful learning experience. This research uses a quantitative approach with a quasi-experimental research design. The sample consisted of 12 students from SD Istianah Terpadu, Sorong City. Data weqare gathered through a questionnaire and analyzed using SPSS to test the proposed hypothesis. The study results indicated significant differences in the average, maximum, and minimum scores before and after the treatment. The significance value was 0.000 < 0.05, which leads to the rejection of H0 and the acceptance of H1. This suggests that there is a difference in the average learning interest before and after the treatment, indicating that the implementation of the role playing method effectively enhances students' learning interest in Indonesian Language subject for fourth-grade students at SD Istianah Terpadu Sorong City.